Dietary supplementation of fermented lemon peel enhances lysozyme activity and susceptibility to Photobacterium damselae for orange-spotted grouper, Epinephelus coioides. Issue 117 (October 2021) - Zhuo, Li-Chao; Chen, Chien-Fu; Lin, Yu-Hung
Abstract: The waste recycling of lemon peel, as a functional feed additive in aquafeed was evaluated by estimating the effects of fermented lemon peel (FLP) supplementation in diet on growth performance, innate immune responses, and susceptibility to Photobacterium damselae of grouper, Epinephelus coioides . A basal diet was added FLP at 0%, 1%, 3%, and 5%. Four tested diets were each fed to juvenile grouper (initial weight: 15.89 ± 0.10 g, triplicate groups) in a recirculation rearing system for eight weeks. Fish fed diets with 0%–3% FLP exhibited higher ( p < 0.05) final weight, weight gain, and feed efficiency than fish fed the 5% FLP-diet. After challenge test, fish fed the 3% FLP-diet appeared the lowest mortality, followed by fish fed the 1% FLP-diet, and lowest in fish fed 0% and 5% FLP-diets. Plasma lysozyme activities were higher in fish fed diets with FLP than in fish fed the FLP-free control diet before challenge test. After challenge, fish fed diets with 1% and 3% FLP showed highest lysozyme activities, followed by fish fed the diet with 5% FLP, and lowest in fish fed the control diet. Hepatic malondialdehyde content was higher in fish fed the control diet than in fish fed diets with 1%–3% FLP. Results found that diets supplemented with 1%–3% fermented lemon peel can enhance lysozyme activity and resistance to pathogen P. damselae of grouper. Highlights: Lemon peel fermented with Lactobacillus plantarum supplemented in diet at 1–3% didn't negatively affect growth of grouper. Diets with 1–3% fermented lemon peel reduced oxidative status and enhanced lysozyme activity for the fish. Diets with 1%–3% fermented lemon peel enhanced resistance to Photobacterium damselae for the species. The fermented lemon peel can be potentially used as a functional feed additive.